2010
DOI: 10.1002/jmri.22400
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the apparent diffusion coefficient value and dynamic magnetic resonance imaging findings with prognostic factors in invasive ductal carcinoma

Abstract: Purpose: To evaluate the correlation of the mean and minimal apparent diffusion coefficient values (ADC mean , ADC minimal ) and dynamic magnetic resonance imaging (MRI) findings with prognostic factors in invasive ductal carcinoma. Materials and Methods:A total of 107 women with invasive ductal cancer underwent breast MRI. The ADC mean and ADC minimal of the cancers were computed. MRI findings were retrospectively evaluated according to the Breast Imaging Reporting and Data System (BI-RADS) lexicon: mass or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
116
3
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(137 citation statements)
references
References 66 publications
10
116
3
3
Order By: Relevance
“…Breast MRI is an established supplemental technique to mammography and ultrasonography for evaluation of suspicious breast lesions. Diffusion-weighted MRI (DWI) has recently been integrated into the standard breast MRI for discrimination of benign and malignant breast lesions obtained with dynamic contrast-enhanced MRI [1][2][3][4][5][6][7][8][9][10][11][12][13]. DWI is a non-invasive technique that represents the biological character of the mainly Brownian movement of protons in bulk water molecules in vivo.…”
mentioning
confidence: 99%
“…Breast MRI is an established supplemental technique to mammography and ultrasonography for evaluation of suspicious breast lesions. Diffusion-weighted MRI (DWI) has recently been integrated into the standard breast MRI for discrimination of benign and malignant breast lesions obtained with dynamic contrast-enhanced MRI [1][2][3][4][5][6][7][8][9][10][11][12][13]. DWI is a non-invasive technique that represents the biological character of the mainly Brownian movement of protons in bulk water molecules in vivo.…”
mentioning
confidence: 99%
“…In this regard, we postulated that DWI may be valuable in the detection of LNM since it exhibits reduced ADC values in malignant BC. Several studies have illustrated that LNM in BC may be evaluated via the ADC quantified by DWI (Fornasa et al, 2012;Luo et al, 2012), while other documents also reported contradictory findings (Jeh et al, 2011;Choi et al, 2012). Therefore, the present meta-analysis was performed to assess the feasibility of DWI in the diagnosis of LNM in BC.…”
Section: Introductionmentioning
confidence: 94%
“…Additionally, as for the step of screening, a flow chart of the study selection process was displayed in Figure 1. Initially, a total of 603 papers were selected from the 9 databases through screening the title and key words (Nakajo et al, 2010;Razek et al, 2010;Jeh et al, 2011;Nakai et al, 2011;Choi et al, 2012;Fornasa et al, 2012;Luo et al, 2012;Kamitani et al, 2013;Luo et al, 2013). Followed by excluding the duplicates (n=2), letters, reviews or meta-analysis (n=128), non-human studies (n=137), and the studies not related to research topics (n=145), the left studies (n=191) were reviewed and additional 179 studies were excluded in that they were not case-control or cohort study (n=48), not relevant to diffusion MRI (n=62), or not relevant to BC (n=69).…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Less aggressive tumors (Grade 1 and in situ lesions) displayed an average ADC value of 1.19×10 -3 mm 2 /s, whereas more aggressive tumors (Grades 2 and 3) had an average ADC value of 0.96×10 -3 mm 2 /s. Another study found a significant correlation between the average ADC value of invasive ductal carcinoma of the breast and estrogen receptor (ER) and HER2 expression (47).…”
Section: Breast Applicationsmentioning
confidence: 99%